Peppermint and caraway oils have muscle inhibitory and pro‐secretory activity in the human intestine in vitro. Issue 2 (15th October 2019) - Krueger, Dagmar; Schäuffele, Stefanie; Zeller, Florian; Demir, Ihsan Ekin; Theisen, Jörg; Michel, Klaus; Schemann, Michael
Abstract: Background: Herbal medicinal products with a broad activity spectrum may be promising alternatives to treat functional gastrointestinal disorders (FGD). Menthacarin ® is a drug with a fixed combination of peppermint and caraway oils, which is clinically used to treat FGD‐associated symptoms. Materials: We studied the effects of peppermint and caraway oils on contractile and secretory activity in 255 human small and large intestinal preparations derived from surgical resections (73 patients). Motility was recorded in circular smooth muscle strips and secretion with the Ussing chamber‐voltage clamp technique. Electrical field stimulation evoked nerve induced contractile responses. Key Results: Peppermint and caraway oil concentrations dependently inhibited muscle contractility as indicated by sustained muscle relaxation and decrease in phasic contractility. These effects occurred in small and large intestinal preparations with IC50 values ranging between 17 and 90 µg/mL for peppermint oil and between 7 and 127 µg/mL for caraway oil. Neither peppermint nor caraway oil influenced the nerve evoked contractile response. The inhibition of contractile activity, but not the muscle relaxation, was prevented by the L‐type calcium channel activator Bay K8644 but not by the neurotoxin tetrodotoxin. Both peppermint oil and caraway oil increased epithelial secretion, which remained in tetrodotoxin. Conclusion & Interference: The findings revealed a strong muscle inhibitory and pro‐secretory action of peppermint and caraway oils at clinically relevant concentrations. Both actions were nerve‐independent. The inhibition of contractility was mediated by inhibition of L‐type calcium channels. The effects on muscle and epithelial activity may contribute to the beneficial effects observed in patients with FGD. Abstract : Peppermint and caraway oils are widely used as alternative medical treatment of symptoms associated with functional gut disorder. We aimed to reveal their effects on human motility and secretion in vitro. Both oils had muscle inhibitory and pro‐secretory effects which were due to direct inhibition of smooth muscle and direct activation of epithelium. The effects on muscle and epithelial activity may contribute to the beneficial effects observed in patients with functional gut disorders.